2020
DOI: 10.2147/opth.s269179
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Experience in the Administration of Intravitreal Injection Therapy at a Tertiary University Hospital in Jordan During the COVID-19 Lockdown</p>

Abstract: Purpose: To describe the clinical experience with the delivery of intravitreal injection therapy to patients with various indications at a tertiary university hospital during the COVID-19 lockdown in Jordan. Methods: This is a retrospective observational study of patients who received intravitreal injections between April 12th and May 9th, 2020, a period during the national COVID-19 lockdown (March 16th to June 6th, 2020). Special medical and logistic arrangements, priority and visual risk assessment and stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 25 publications
1
45
0
2
Order By: Relevance
“…Saleh et al reported that intravitreal injections were safely delivered, without any know Covid-19 case transmission in a tertiary care clinic in Jordan, but clinical volumes were diminished due to patient fears regarding contracting the virus. 15 Moreover, those who did seek care had poorer presenting visual acuity. Two studies from Milan, Italy also documented decreased clinical (up to 71%) and injection (54–58%) volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Saleh et al reported that intravitreal injections were safely delivered, without any know Covid-19 case transmission in a tertiary care clinic in Jordan, but clinical volumes were diminished due to patient fears regarding contracting the virus. 15 Moreover, those who did seek care had poorer presenting visual acuity. Two studies from Milan, Italy also documented decreased clinical (up to 71%) and injection (54–58%) volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Both randomised controlled trials and real-world data analyses have demonstrated the benefit of anti-VEGF injections in the treatment of medical retina conditions. Studies suggest that without intravitreal treatment, there will be a significant deterioration in patients’ vision [ 6 9 ]. With this evidence, it can be predicted that the delays to anti-VEGF treatment attributed to COVID-19 will have a significant negative impact on visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic changed the whole world. Since social distancing is a key measure to slow the transmission of the virus, in many countries, governments decided to implement lockdowns [4][5]. Although necessary to control the pandemic, these measures have resulted in major interruptions in the economy, social life, and healthcare provision [4].…”
Section: Introductionmentioning
confidence: 99%